2016
DOI: 10.1371/journal.pone.0164763
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Acts via the JAK2/STAT3 Pathway to Attenuate Isoflurane-Induced Neurocognitive Deficits in Senile Mice

Abstract: BackgroundPrevious studies showed that isoflurane-induced cognitive deficits could be alleviated by dexmedetomidine in young animal subjects. In the current study, we examine whether dexmedetomidine could also alleviate isoflurane-induced cognitive deficits in senile animals.MethodsSenile male C57BL/6 mice (20 months) received dexmedetomidine (50 μg/kg, i.p.) or vehicle 30 minutes prior to isoflurane exposure (1.3% for 4 h). Cognitive function was assessed 19 days later using a 5-day testing regimen with Morri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Interestingly, in the DEX 50 mg kg À1 group we found a significant increase in apoptosis in the CA1 region of the hippocampus. A high sensitivity of the CA1 region of the hippocampus to DEX has also been observed in neonatal mice treated with DEX 50 mg kg À1 alone, 67 suggesting that this region is particularly sensitive to high doses of DEX in the developing brain. However, Pancaro and colleagues 65 found that DEX alone (30 or 45 mg kg À1 ) induced significant apoptosis in sensorial cortical regions including the S1 region but not in the hippocampus.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in the DEX 50 mg kg À1 group we found a significant increase in apoptosis in the CA1 region of the hippocampus. A high sensitivity of the CA1 region of the hippocampus to DEX has also been observed in neonatal mice treated with DEX 50 mg kg À1 alone, 67 suggesting that this region is particularly sensitive to high doses of DEX in the developing brain. However, Pancaro and colleagues 65 found that DEX alone (30 or 45 mg kg À1 ) induced significant apoptosis in sensorial cortical regions including the S1 region but not in the hippocampus.…”
Section: Discussionmentioning
confidence: 92%
“…↓: enhanced; ⊥: attenuated; AKI: acute kidney injury; DEX: dexmedetomidine; GSK-3β: glycogen synthase kinase-3β; HO-1: heme oxygenase-1; IL-6: interleukin 6; IL-18: interleukin 18; IL-1β: interleukin-1β; LPS: lipopolysaccharide; NQO1: NAD(P)H quinone oxidoreductase-1; Nrf2: nuclear factor erythroid 2-related factor 2; ROS: reactive oxygen species; SB216763: GSK-3β inhibitor; TNF-α: tumor necrosis factor α [Color figure can be viewed at wileyonlinelibrary.com] DEX is thought to exert its organoprotective effects mainly by binding to α2-AR . The concentrations of DEX (25 μg/kg) and Atip (250 μg/kg) used in the present study were based on previous work (Cui et al, 2015b;Si et al, 2016) and on a binding affinity ratio of 10:1 for the agonist-antagonist (Virtanen, Savola, & Saano, 1989). The IRs (I 1 R, I 2 R, I 3 R) are another class of DEX-binding receptors that have mainly been investigated for their involvement in anesthesia and analgesia (H. Zhang, Yan, et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…To illuminate the molecular mechanisms by which TCTN1 affected thyroid cancer apoptosis, we detected some molecules associated with cell survival in CAL62 cells after TCTN1 knockdown. The anti-apoptotic protein Bcl-2 plays a pivotal role in regulating cell apoptosis under many adverse conditions, while pro-apoptotic Bad is essential for inducing apoptosis ( 22 ). In our results, reduced Bcl-2 and increased Bad expression suggested silencing TCTN1 might serve as a promoter of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%